2014
DOI: 10.5858/arpa.2012-0227-oa
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Patterns of a Disintegrin and Metalloproteinase With Thrombospondin Motifs (ADAMTS) -1, -4, -5, and -14 in Human Placenta and Gestational Trophoblastic Diseases

Abstract: Context.-The ability of intermediate trophoblasts to invade maternal tissue during placentation depends on how well they can degrade the extracellular matrix. Invasion into the extracellular matrix requires many complex proteases. A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) is a novel family of secreted metalloproteinases. The ADAMTS-1, -4, -5, and -14 subtypes are known to be expressed in human placenta, but little is understood about their expression patterns.Objective.-To examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…Functionally, it is responsible for the degradation of aggrecan [37][38][39]. Increasing evidence has shown that the dysregulation of ADAMTS4 expression involves in the tumorigenesis of some tumor, such as melanoma, head and neck cancer, Ewing's sarcoma, and choriocarcinoma [40][41][42][43][44]. In this study, we accomplished a gene expression profile and silico analysis and found that the rs28599926 polymorphism significantly downregulated ADAMTS4 expression.…”
Section: Mirna Polymorphism and Afb1-relaed Hccmentioning
confidence: 92%
“…Functionally, it is responsible for the degradation of aggrecan [37][38][39]. Increasing evidence has shown that the dysregulation of ADAMTS4 expression involves in the tumorigenesis of some tumor, such as melanoma, head and neck cancer, Ewing's sarcoma, and choriocarcinoma [40][41][42][43][44]. In this study, we accomplished a gene expression profile and silico analysis and found that the rs28599926 polymorphism significantly downregulated ADAMTS4 expression.…”
Section: Mirna Polymorphism and Afb1-relaed Hccmentioning
confidence: 92%
“…For successful placentation, the transformation cytotrophoblasts into intermediate trophoblast and the invasion of these cells into maternal tissues are needed (31). During placenta formation, extravillous trophoblasts lose their cell-cell interactions and secrete various proteases, including ADAMTS1.…”
Section: Pregnancy and Adamtsmentioning
confidence: 99%
“…In ADAMTS1 knockout mice, it was observed that the pregnancy rate declined (33). ADAMTS4 and -5 are expressed at very high levels, especially in the first-trimester placenta and are responsible for maternal tissue invasion (31). ADAMTS5 presence in first-trimester decidual endometrial tissue was determined.…”
Section: Pregnancy and Adamtsmentioning
confidence: 99%
“…Human ADAMTS4 (also known as ADMP‐1 , ADAMTS‐2 , or ADAMTS‐4 ), a major member of ADAMTS family genes, is an important aggrecanase involving in collagen maturation, matrix degradation, organogenesis, and blood coagulation . In the past several decades, the epidemiological and clinicopathological studies have shown that the dysregulation of ADAMTS4 expression and function may involve in the process of some tumors, including head and neck cancer, melanoma, choriocarcinoma, and Ewing's sarcoma . Demircan et al investigated the expression of ADAMTS4 mRNA in primary head and neck squamous cell carcinoma with and without metastasis by quantitative real time polymerase chain reaction technique and found that higher expression was in the metastatic tumor tissues.…”
Section: Discussionmentioning
confidence: 99%